2014
DOI: 10.1186/1754-6834-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale structural and chemical analysis of sugarcane bagasse in the process of sequential acid–base pretreatment and ethanol production by Scheffersomyces shehatae and Saccharomyces cerevisiae

Abstract: BackgroundHeavy usage of gasoline, burgeoning fuel prices, and environmental issues have paved the way for the exploration of cellulosic ethanol. Cellulosic ethanol production technologies are emerging and require continued technological advancements. One of the most challenging issues is the pretreatment of lignocellulosic biomass for the desired sugars yields after enzymatic hydrolysis. We hypothesized that consecutive dilute sulfuric acid-dilute sodium hydroxide pretreatment would overcome the native recalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(105 citation statements)
references
References 54 publications
15
78
0
12
Order By: Relevance
“…The two peaks of CH2 symmetric and CH asymmetric stretching respectively were present at 2850 cm −1 and 2918 cm −1 being characteristic of cellulose [25]. The slight disturbances in the CS-EtIm [Ac]+Na and CS-BmIm [Ac]+Na peak at 2850 cm −1 indicated that after these pretreatments, the cellulose chain had been affected [26]. In short, the presence of lignocellulosic matrix was confirmed by these bands.…”
Section: Ftir Spectra Analysismentioning
confidence: 65%
“…The two peaks of CH2 symmetric and CH asymmetric stretching respectively were present at 2850 cm −1 and 2918 cm −1 being characteristic of cellulose [25]. The slight disturbances in the CS-EtIm [Ac]+Na and CS-BmIm [Ac]+Na peak at 2850 cm −1 indicated that after these pretreatments, the cellulose chain had been affected [26]. In short, the presence of lignocellulosic matrix was confirmed by these bands.…”
Section: Ftir Spectra Analysismentioning
confidence: 65%
“…When comparing these values with the literature values (Rainey 2009;da Silva et al 2010;Rocha et al 2011;Rabelo et al 2011;Canilha et al 2012 andChandel et al 2014), it can be observed that there is not much difference. The pre-treatment of substrate with 3% H2SO4 decreased the proportion of hemicellulose and lignin and increased the cellulose content for both depithed and mill-run bagasse, which was predictable since the acid pretreatment was used to remove hemicellulose.…”
Section: Pretreatmentmentioning
confidence: 87%
“…The region between 1,200 and 1,100 cm -1 is a large contribution of hemicellulose and cellulose, which exhibits a maximum value around 1,035 cm -1 due to C-O stretching and 1,164 cm -1 for the asymmetrical stretching of C-O-C (Pandey 1999;Colom et al 2003;Pandey 2005;Chandel et al 2014). The region around 1,247 cm -1 was due to the stretching of C-O, which is characteristic of hemicellulose and lignin (Pandey and Pitman 2003;Chandel et al 2014). A band around 1,458 cm -1 is reported to be a deformation of lignin CH2 and CH3, and 1,604 cm -1 is reported to be stretching of the C=C and C=O lignin aromatic ring.…”
Section: Characterisation Of Raw and Pre-treated Bagasse Fourier Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a good way to solve the problem of wasted cellulose resources and a lack of energy. [7][8][9] Lignocellulose widely exists in grains, beans, maize, rice, and some subsidiary agricultural products. Using lignocellulose in the feed industry is another important application.…”
Section: Introductionmentioning
confidence: 99%